Sinergisitas KB Bina Mulya Konservasi Kaliangkrik dan TPQ Tibbil Qulub Dalam Upaya Pengenalan Ibadah Sholat - Nginayatul Maghfiroh; Lilis Madyawati; Reza Edwin Sulistyaningtyas (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Synergy between Early Childhood Education institutions and non-formal religious education plays a crucial role in establishing worship habits from an early age, as early childhood represents a developmental stage highly responsive to habituation and role modeling. The introduction of shalat (Islamic prayer) requires an integrated approach so that children not only recognize prayer movements and recitations but also gradually develop understanding and religious attitudes. This study aims to describe the forms of synergy between KB Bina Mulya Konservasi Kaliangkrik and TPQ Tibbil Qulub in introducing shalat to early childhood learners. The research employed a qualitative approach with a phenomenological design. The subjects of the study were KB and TPQ teachers, and data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validity ensured through source triangulation. The findings reveal intensive communication between teachers, alignment of instructional materials, and collaboration in habituation and prayer practice. This synergy positively contributes to improving children’s understanding, skills, and religious attitudes in performing shalat.